MiR-98 and let-7g* Protect the Blood-Brain Barrier Under Neuroinflammatory Conditions. Issue 12 (December 2015) - Rom, Slava; Dykstra, Holly; Zuluaga-Ramirez, Viviana; Reichenbach, Nancy L; Persidsky, Yuri
Pathologic conditions in the central nervous system, regardless of the underlying injury mechanism, show a certain level of blood-brain barrier (BBB) impairment. Endothelial dysfunction is the earliest event in the initiation of vascular damage caused by inflammation due to stroke, atherosclerosis, trauma, or brain infections. Recently, microRNAs (miRNAs) have emerged as a class of gene expression regulators. The relationship between neuroinflammation and miRNA expression in brain endothelium remains unexplored. Previously, we showed the BBB-protective and anti-inflammatory effects of glycogen synthase kinase (GSK) 3β inhibition in brain endothelium in in vitro and in vivo models of neuroinflammation. Using microarray screening, we identified miRNAs induced in primary human brain microvascular endothelial cells after exposure to the pro-inflammatory cytokine, tumor necrosis factor-α, with/out GSK3β inhibition. Among the highly modified miRNAs, let-7 and miR-98 were predicted to target the inflammatory molecules, CCL2 and CCL5. Overexpression of let-7 and miR-98 in vitro and in vivo resulted in reduced leukocyte adhesion to and migration across endothelium, diminished expression of pro-inflammatory cytokines, and increased BBB tightness, attenuating barrier 'leakiness' in neuroinflammation conditions. For the first time, we showed that miRNAs could be used as a therapeutic tool to prevent the BBB dysfunction in neuroinflammation.